Thermodynamically modulated partially double-stranded linear DNA probe design for homogeneous real-time PCR - Huang, Shihai (Oxford University Press, 2007)
Real-time PCR assays have recently been developed for diagnostic and research purposes. Signal generation in real-time PCR is achieved with probe designs that usually depend on exonuclease activity of DNA polymerase (e.g. TaqMan probe) or oligonucleotide hybridization (e.g. molecular beacon). Probe design often needs to be specifically tailored either to tolerate or to differentiate between sequence variations. The conventional probe technologies offer limited flexibility to meet these diverse requirements. Here, we introduce a novel partially double-stranded linear DNA probe design. It consists of a hybridization probe 5′-labeled with a fluorophore and a shorter quencher oligo of complementary sequence 3′-labeled with a quencher. Fluorescent signal is generated when the hybridization probe preferentially binds to amplified targets during PCR. This novel class of probe can be thermodynamically modulated by adjusting (i) the length of hybridization probe, (ii) the length of quencher oligo, (iii) the molar ratio between the two strands and (iv) signal detection temperature. As a result, pre-amplification signal, signal gain and the extent of mismatch discrimination can be reliably controlled and optimized. The applicability of this design strategy was demonstrated in the Abbott RealTime HIV-1 assay.